Internal Audit Quality in the Public Sector vs Private Sector : Literature Analysis - Muhammad Irsan Nasution; Yulisfan Yulisfan (Proceeding of The International Conference on Business and Economics, 2024)
This study analyzes the differences and similarities of internal audit quality in the public sector and private sector using a literature analysis approach. The main objective was to explore factors that affect audit quality, such as auditor independence, competence, transparency, and accountability. The results show that the public sector often faces challenges in maintaining auditor independence due to the influence of bureaucracy and politicization. However, the sector has advantages in transparency and accountability, which support public trust in the management of public funds. In contrast, the private sector excels in operational efficiency and flexibility, supported by the use of modern audit technology and leaner organizational structures. Despite the differences, both sectors require high auditor competence and strong internal control systems to ensure audit effectiveness. This research suggests strengthening auditor training, implementing modern audit technology, and increasing collaboration between internal and external auditors to ensure audit objectivity and quality. In addition, further studies are recommended to explore the impact of applying new technologies, such as big data and artificial intelligence, and conduct cross-sectoral comparisons to understand audit implementation globally.